Expansion of Indonesian Trade in the Pacific Region Through Increasing Indonesian Trade - Papua New Guinea - Gebriella Sagina Hutabarat; Akim; Darmansjah Djumala (Journal of Law, Politic and Humanities, 2024)
This article discusses the expansion of Indonesia's trade in the Pacific region, with a specific focus on enhancing trade relations between Indonesia and Papua New Guinea. In recent years, Indonesia has sought to strengthen its position as a key trading partner in the region by leveraging the rich natural resources of Papua New Guinea and improving market access. This research analyzes the factors influencing the trade relationship between the two countries, including trade policies, regulatory quality, and the challenges faced in increasing trade flows. Furthermore, the article explores the potential for collaboration in strategic sectors such as agriculture, fisheries, and renewable energy, as well as how both countries can address existing obstacles to maximize the benefits of trade cooperation. The research findings indicate that through appropriate policies and enhanced bilateral cooperation, Indonesia can increase trade volume and make a significant contribution to the economic development of both countries in the Pacific region.